Enhancement of X-ray emission from nanocolloidal gold suspensions under double-pulse excitation - Hsu, Wei-Hung; Masim, Frances Camille P.; Balčytis, Armandas; Huang, Hsin-Hui; Yonezawa, Tetsu; Kuchmizhak, Aleksandr A.; Juodkazis, Saulius; Hatanaka, Koji (Beilstein Journal of Nanotechnology, 2018)
Enhancement of X-ray emission was observed from a micro-jet of a nano-colloidal gold suspension in air under double-pulse excitation of ultrashort (40 fs) near-IR laser pulses. Temporal and spatial overlaps between the pre-pulse and the main pulse were optimized for the highest X-ray emission. The maximum X-ray intensity was obtained at a 1–7 ns delay of the main pulse irradiation after the pre-pulse irradiation with the micro-jet position shifted along the laser beam propagation. It was revealed that the volume around gold nanoparticles where the permittivity is near zero, ε ≈ 0, accounts for the strongest absorption, which leads to the effective enhancements of X-ray emission.
Keywords: double pulse; gold nanoparticles; intense femtosecond laser; plasma; water; X-ray

(untitled) - Sakdinawat, A.; Attwood, D. (Nat. Photonics, 2010)

(untitled) - Mondal, S.; Chakraborty, I.; Ahmad, S.; Carvalho, D.; Singh, P.; Lad, A. D.; Narayanan, V.; Ayyub, P.; Kumar, G. R.; Zheng, J.; Sheng, Z. M. (Phys. Rev. B, 2011)

The Physics of Laser-Plasma Interaction - Kruer, W. L. (Addison-Wesley, 1988)

The Physics of Laser-Plasma Interaction - Kruer, W. L. (Addison-Wesley, 1988)

(untitled) - Liu, X.-L.; Lu, X.; Liu, X.; Xi, T.-T.; Liu, F.; Ma, J.-L.; Zhang, J. (Opt. Express, 2010)

(untitled) - Gamaly, E. G. (Phys. Rep., 2011)

(untitled) - Bargheer, M.; Zhavoronkov, N.; Gritsai, Y.; Woo, J. C.; Kim, D. S.; Woerner, M.; Elsaesser, T. (Science, 2004)

(untitled) - Lee, T.; Jiang, Y.; Rose-Petruck, C. G.; Benesch, F. (J. Chem. Phys., 2005)

(untitled) - Hatanaka, K.; Fukumura, H. (X-Ray Spectrom., 2012)

(untitled) - Bulanov, S. V.; Kovrizhnykh, L. M.; Sakharov, A. S. (Phys. Rep., 1990)

(untitled) - Stearns, D. G.; Landen, O. L.; Campbell, E. M.; Scofield, J. H. (Phys. Rev. A, 1988)

(untitled) - Delfour, L.; Itina, T. E. (J. Phys. Chem. C, 2015)

(untitled) - Bauer, D.; Brabec, T.; Fehske, H.; Lochbrunner, S.; Meiwes-Broer, K.-H.; Redmer, R. (New J. Phys., 2013)

(untitled) - Wopperer, P.; Dinh, P. M.; Reinhard, P.-G.; Suraud, E. (Phys. Rep., 2015)

(untitled) - Link, S.; El-Sayed, M. A. (J. Phys. Chem. B, 1999)

(untitled) - Huang, H.-h.; Nagashima, T.; Hsu, W.-h.; Juodkazis, S.; Hatanaka, K. (Nanomaterials, 2018)

(untitled) - Masim, F. C. P.; Porta, M.; Hsu, W.-H.; Nguyen, M. T.; Yonezawa, T.; Balčytis, A.; Juodkazis, S.; Hatanaka, K. (ACS Photonics, 2016)

(untitled) - Hatanaka, K.; Porta, M.; Masim, F. C. P.; Hsu, W.-H.; Nguyen, M. T.; Yonezawa, T.; Balčytis, A.; Juodkazis, S. (arXiv, 2016)

(untitled) - Passig, J.; Irsig, R.; Truong, N. X.; Fennel, T.; Tiggesbäumker, J.; Meiwes-Broer, K. H. (New J. Phys., 2012)

(untitled) - Wong, L. J.; Kaminer, I.; Ilic, O.; Joannopoulos, J. D.; Soljačić, M. (Nat. Photonics, 2016)

(untitled) - Grillet, N.; Manchon, D.; Cottancin, E.; Bertorelle, F.; Bonnet, C.; Broyer, M.; Lermé, J.; Pellarin, M. (J. Phys. Chem. C, 2013)

(untitled) - Knight, M. W.; King, N. S.; Liu, L.; Everitt, H. O.; Nordlander, P.; Halas, N. J. (ACS Nano, 2014)

(untitled) - Rousse, A.; Audebert, P.; Geindre, J. P.; Falliès, F.; Gauthier, J. C.; Mysyrowicz, A.; Grillon, G.; Antonetti, A. (Phys. Rev. E, 1994)

(untitled) - Winkler, T.; Haahr-Lillevang, L.; Sarpe, C.; Zielinski, B.; Götte, N.; Senftleben, A.; Balling, P.; Baumert, T. (Nat. Phys., 2017)

(untitled) - Hatanaka, K.; Miura, T.; Fukumura, H. (Appl. Phys. Lett., 2002)

(untitled) - Hatanaka, K.; Ono, H.; Fukumura, H. (Appl. Phys. Lett., 2008)

(untitled) - Hatanaka, K.; Miura, T.; Fukumura, H. (Chem. Phys., 2004)

(untitled) - Hsu, W.-H.; Masim, F. C. P.; Balčytis, A.; Juodkazis, S.; Hatanaka, K. (Opt. Express, 2017)

(untitled) - Sandhu, A. S.; Kumar, G. R.; Sengupta, S.; Das, A.; Kaw, P. K. (Phys. Rev. Lett., 2005)

(untitled) - Eder, D. C.; Pretzler, G.; Fill, E.; Eidmann, K.; Saemann, A. (Appl. Phys. B: Lasers Opt., 2000)

(untitled) - Pisani, F.; Andiel, U.; Eidmann, K.; Witte, K.; Uschmann, I.; Morak, A.; Förster, E.; Sauerbrey, R. (Appl. Phys. Lett., 2004)

(untitled) - Bastús, N. G.; Comenge, J.; Puntes, V. (Langmuir, 2011)

(untitled) - Jana, N. R.; Gearheart, L.; Murphy, C. J. (Adv. Mater., 2001)

(untitled) - Masim, F. C. P.; Hsu, W.-H.; Liu, H.-L.; Yonezawa, T.; Balčytis, A.; Juodkazis, S.; Hatanaka, K. (Opt. Express, 2017)

(untitled) - Hsu, W.-H.; Masim, F. C. P.; Porta, M.; Nguyen, M. T.; Yonezawa, T.; Balčytis, A.; Wang, X.; Rosa, L.; Juodkazis, S.; Hatanaka, K. (Opt. Express, 2016)

(untitled) - Gamaly, E. G.; Rode, A. V. (Appl. Phys. A: Mater. Sci. Process., 2018)

(untitled) - Gamaly, E. G.; Rode, A. V.; Luther-Davies, B.; Tikhonchuk, V. T. (Phys. Plasmas, 2002)

(untitled) - Linz, N.; Freidank, S.; Liang, X.-X.; Vogelmann, H.; Trickl, T.; Vogel, A. (Phys. Rev. B, 2015)

(untitled) - Wang, X. W.; Kuchmizhak, A. A.; Li, X.; Juodkazis, S.; Vitrik, O. B.; Kulchin, Y. N.; Zhakhovsky, V. V.; Danilov, P. A.; Ionin, A. A.; Kudryashov, S. I.; Rudenko, A. A.; Inogamov, N. A. (Phys. Rev. Appl., 2017)

(untitled) - Baumgart, J.; Humbert, L.; Boulais, É.; Lachaine, R.; Lebrun, J.-J.; Meunier, M. (Biomaterials, 2012)

(untitled) - Boulais, É.; Lachaine, R.; Meunier, M. (Nano Lett., 2012)

(untitled) - Muto, H.; Miyajima, K.; Mafuné, F. (J. Phys. Chem. C, 2008)

(untitled) - Pyatenko, A.; Yamaguchi, M.; Suzuki, M. (J. Phys. Chem. C, 2009)

(untitled) - Boutopoulos, C.; Hatef, A.; Fortin-Deschênes, M.; Meunier, M. (Nanoscale, 2015)

(untitled) - Nakajima, T.; Wang, X.; Chatterjee, S.; Sakka, T. (Sci. Rep., 2016)

(untitled) - Guck, J.; Ananthakrishnan, R.; Mahmood, H.; Moon, T. J.; Cunningham, C. C.; Käs, J. (Biophys. J., 2001)

(untitled) - Shih, C.-Y.; Shugaev, M. V.; Wu, C.; Zhigilei, L. V. (J. Phys. Chem. C, 2017)

(untitled) - Wang, L.; Chen, Q.-D.; Cao, X.-W.; Buividas, R.; Wang, X.; Juodkazis, S.; Sun, H.-B. (Light: Sci. Appl., 2017)

(untitled) - Masim, F. C. P.; Liu, H.-L.; Porta, M.; Yonezawa, T.; Balčytis, A.; Juodkazis, S.; Hsu, W.-H.; Hatanaka, K. (Opt. Express, 2016)

(untitled) - Huang, H. J.; Yu, C.-p.; Chang, H. C.; Chiu, K. P.; Ming Chen, H.; Liu, R. S.; Tsai, D. P. (Opt. Express, 2007)

(untitled) - Jin, Q.; E, Y.; Williams, K.; Dai, J.; Zhang, X.-C. (Appl. Phys. Lett., 2017)

(untitled) - Dey, I.; Jana, K.; Fedorov, V. Y.; Koulouklidis, A. D.; Mondal, A.; Shaikh, M.; Sarkar, D.; Lad, A. D.; Tzortzakis, S.; Couairon, A.; Kumar, G. R. (Nat. Commun., 2017)

(untitled) - Balakin, A. V.; Dzhidzhoev, M. S.; Gordienko, V. M.; Esaulkov, M. N.; Zhvaniya, I. A.; Ivanov, K. A.; Kotelnikov, I. A.; Kuzechkin, N. A.; Ozheredov, I. A.; Panchenko, V. Y.; Savel’ev, A. B.; Smirnov, M. B.; et al. (IEEE Trans. Terahertz Sci. Technol., 2017)

(untitled) - Hamster, H.; Sullivan, A.; Gordon, S.; White, W.; Falcone, R. W. (Phys. Rev. Lett., 1993)

(untitled) - Zhang, X. C.; Shkurinov, A.; Zhang, Y. (Nat. Photonics, 2017)